PENGARUH PEMBERIAN ELISITOR EKSTRAK KHAMIR Saccharomyces cerevisiae Hansen TERHADAP KANDUNGAN AJMALISIN DALAM KULTUR AGREGAT SEL Catharanthus roseus (L.) G. Don. - Jujun Ratnasari; Arbayah H Siregar; Rizkita RE (Research Center for Biology-Indonesian Institute of Sciences, 2001)
There were many ways to obtain high production of secondary metabolites in plant tissue culture; among the other is elicitation.An experiment to study the effect of elicitor derived from Saccharomyces cerevisiae Hansen extract on ajmalicine content in cell aggregates culture of Catharanthus roseus (L.) G.Don, has been conducted. The media used for callus induction and cell aggregates culture were Zenk 6 5(1977) with addition of 2.5 x 10